Student Assessments of Early Childhood Caries in Some Informal Settlements of Cape Town: A 10‐Year Series of Cross‐Sectional Studies - Larisa Krekmanova; Neil Myburgh; Ted Lundgren (Public Health Challenges)
ABSTRACT Aim To assess Early Childhood Caries by measuring the dmft, Significant Caries Index (SiC), pufa, and caries‐free status in informal settlements outside Cape Town, South Africa over a 10‐year period. Method A series of cross‐sectional studies over a 10‐year period (2009–2019). Surveys were carried out in preschools in informal settlements. A total of 5090 children aged from 1 to 5 years of age were examined. Results For 1‐ to 3‐year‐olds, the mean dmft was 4.33 ± 1.55, and for 4‐ and 5‐year‐olds, it was 6.34 ± 1.48. The difference in dmft for 1‐ to 3‐year‐olds increased but did not differ statistically between 2009 and 2019. For 4–5 years old, there was an increase over time. For 1‐ to 3‐year‐olds, the mean pufa was 0.34 ± 0.28, and for 4‐ to 5‐year‐olds, it was 0.63 ± 0.59. For 1‐ to 3‐ and for 4‐ to 5‐year‐olds, there was a statistically significant, lower pufa 2009–2019. For 1‐ to 3‐year‐olds, the mean SiC was 11.0 ± 2.35, and for 4‐ to 5‐year‐olds, it was 12.05 ± 1.89. There was a difference in SiC for 1–3 and for 4‐ to 5‐year‐olds, which was higher but did not differ statistically 2009–2019. Among 1‐ to 3‐year‐olds, 32.1% were assessed as caries‐free. Among 4‐ to 5‐year‐olds, 16.0% were caries‐free. There was a statistically significant, lower number of caries‐free 1‐ to 3‐year‐old and 4‐ 5‐year‐old children 2009–2019. Conclusions The mean dmft has been found to be continuously high from 2009 to 2019. The SiC score remained unchanged, whereas pufa was significantly lower. The frequency of caries‐free children was lower over time.